Should Any Workplace Be Exempt from Smoke-Free Law: The Irish Experience. (24th May 2012) - McCaffrey, M.; Goodman, P.; Gavigan, A.; Kenny, C.; Hogg, C.; Byrne, L.; McLaughlin, J.; Young, K.; Clancy, L.
Abstract : Background . In 2004, the Irish Government introduced national legislation banning smoking in workplaces; with exemptions for "a place of residence". This paper summarises three Irish studies of exempted premises; prisons, psychiatric hospitals and nursing homes. Methods . PM2.5 and nicotine were measured in nursing homes and psychiatric hospitals, in addition to ultrafine particles in the hospitals. In the prisons, officers (n = 30 ) completed exhaled breath Carbon Monoxide (CO) measurements. Questionnaires determined officers' opinion on introducing smoking prohibitions in prisons. Nursing home smoking policies were examined and questionnaires completed by staff regarding workplace secondhand smoke (SHS) exposure. Findings . Ultrafine particle concentrations in psychiatric hospitals averaged 130, 000 cm 3, approximately 45% higher than Dublin pub (35.5 μ g/m 3 ) pre ban. PM2.5 levels in psychiatric hospitals (39.5 μg/m 3 ) were similar to Dublin pubs (35.5 μg/m 3 ) pre ban. In nursing homes permitting smoking, similar PM2.5 levels (33 μ g/m 3 ) were measured, with nicotine levels (0.57 μ g/m 3 ) four times higher than "non-smoking" nursing homes (0.13 μ g/m 3 ). In prisons, 44% of non-smoking officers exhibited exhaled breath CO criteria for light to heavy smokers. Conclusions . With SHS exposure levels in some exempted workplaces similar to Dublin pubs levels pre ban, policies ensuring full protection must be developed and implemented as a right for workers, inmates and patients.